1985
DOI: 10.1002/ana.410180402
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic leteral sclerosis: Part 2. Etiopathogenesis

Abstract: The pathogenesis of the motor neuronal degeneration in amyotrophic lateral sclerosis (ALS) is unclear, though several possible etiological factors are currently being investigated. A unifying hypothesis will have to explain the diverse geographical occurrence, clinical features, and selective vulnerability and relative resistance of different neuronal populations in the disease. It is possible that different biochemical defects underlie this diversity, or alternatively that the many factors incriminated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(33 citation statements)
references
References 136 publications
0
32
0
1
Order By: Relevance
“…Large lumbar motor neurons with a cell body area of ≥450 μm 2 were quantified using the neuronal marker NeuN. Thus, only the large α-motor neurons most vulnerable to cell death in ALS (2,38,39) were quantified, and the γ-type motor neurons that are resistant to the disease were excluded. In SOD1 G93A littermates at the presymptomatic stage, no motor neuron cell death was detected, but by the time of disease onset, only 45.8% of motor neurons had survived, with 19.3% of motor neurons surviving at 120 d of age ( Fig.…”
Section: Atf3 Promotesmentioning
confidence: 99%
“…Large lumbar motor neurons with a cell body area of ≥450 μm 2 were quantified using the neuronal marker NeuN. Thus, only the large α-motor neurons most vulnerable to cell death in ALS (2,38,39) were quantified, and the γ-type motor neurons that are resistant to the disease were excluded. In SOD1 G93A littermates at the presymptomatic stage, no motor neuron cell death was detected, but by the time of disease onset, only 45.8% of motor neurons had survived, with 19.3% of motor neurons surviving at 120 d of age ( Fig.…”
Section: Atf3 Promotesmentioning
confidence: 99%
“…genome-wide association study ͉ single nucleotide polymorphism A myotrophic lateral sclerosis (ALS) is an age-dependent, degenerative disorder of motor neurons (1) that typically develops in the 6th decade and is uniformly fatal, usually within 5 years (2). Approximately 10% of ALS cases are dominantly inherited (3); 20% of these are caused by mutations in the gene encoding copper/zinc superoxide dismutase 1 (SOD1) (4); mutations in the TARDBP gene (5,6) account for Ϸ5% of cases.…”
mentioning
confidence: 99%
“…The existence of risk factors for spo radic ALS has been discussed. The following risk factors have been considered: skeletal trauma, fractures, surgery, hard work and in tense athletic activity [16,17]. Some authors suggested that exposure to heavy metals was a significant factor, but others disagreed [18].…”
Section: Introductionmentioning
confidence: 99%